Psychological Portrait: Empirical Study of the Elderly in the Keputih Social Boarding School Environment, Surabaya - Ayong Lianawati; Veranda Yuniar Maisefa Sefa; Syifa’ul Afidah; Afaf Akiko (Journal of Education and Counseling (JECO), 2022)
Research on "Psychological Portraits: Empirical Studies on the Elderly in the Keputih Social Boarding School Environment in Surabaya". This study aims to obtain an empirical description of the lives of the elderly who live in the Keputih Social Boarding School Environment, Surabaya, the behavior of giving and the behavior of caring for the welfare of others by the community towards neglected elderly. The type of research used is qualitative research using interviews, observation, and documentation. This research was conducted on all socially assisted residents in the Surabaya Keputih Social Institution. The results found when the researchers made observations were how their response was different to their families when they found out that they were placed in the Social Boarding School environment because of the problems that existed in their family life. Some residents who are included in the small group feel happy to be in Liponsos Surabaya, but on the other hand there are also some people who feel unhappy if they are in that environment, because they feel abandoned, not considered by their families. And finally make them think that the family is no longer a home for them. because they feel abandoned, not considered by the family. And finally make them think that the family is no longer a home for them. because they feel abandoned, not considered by the family. And finally make them think that the family is no longer a home for them. Keywords: social cottage, elderly, psychological